The Chirocopter: A UAV for recording sound and video of bats at altitude. Issue 6 (24th March 2018) - Fu, Yanqing; Kinniry, Morgan; Kloepper, Laura N.
Abstract: Most recordings of bats are conducted with fixed equipment, which relies on opportunistic data collection. Unmanned aerial vehicles (UAV; such as drones) are considered inappropriate for recording bats due to ultrasound noise constraints. We developed a UAV system that physically isolates UAV noise, so we can record, with 3D manoeuvrability, ultrasonic audio and spatial thermal data of bat flight at altitude. We tested the noise of our UAV with various payloads and microphone configurations to characterize the ultrasonic noise of our system, physically isolate drone noise from the microphone, and maximize UAV flight performance. Over 84 min of recordings, we captured 3, 847 echolocation signals from bats with corresponding thermal data of bat flight. Our system provides a feasible mechanism to capture both acoustic and video data of bats aloft at flexible locations and altitudes. We include information on how to extend our method to apply to acoustic recordings in the audible (20 Hz–20 kHz) range for recording sounds of other taxa.